Proceedings of the 4th International Workshop on Cooperative and Human Aspects of Software Engineering 2011
DOI: 10.1145/1984642.1984644
|View full text |Cite
|
Sign up to set email alerts
|

A case study of post-deployment user feedback triage

Abstract: Many software requirements are identified only after a product is deployed, once users have had a chance to try the software and provide feedback. Unfortunately, addressing such feedback is not always straightforward, even when a team is fully invested in usercentered design. To investigate what constrains a teams evolution decisions, we performed a 6-month field study of a team employing iterative user-centered design methods to the design, deployment and evolution of a web application for a university commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Other studies (e.g. [7], [9], [18]) support our findings, what makes us confident that the identified problems are real. Ensuring construct validity for empirical studies of software developers is always a complex task, specifically as such studies typically require the researcher to abstract from observed behavior or gathered information.…”
Section: B Limitationssupporting
confidence: 88%
See 2 more Smart Citations
“…Other studies (e.g. [7], [9], [18]) support our findings, what makes us confident that the identified problems are real. Ensuring construct validity for empirical studies of software developers is always a complex task, specifically as such studies typically require the researcher to abstract from observed behavior or gathered information.…”
Section: B Limitationssupporting
confidence: 88%
“…Ko et al [9] found two main factors which constrain evolution decisions in development teams. First, developers were more likely to address feedback they believed to be shared by the majority of the users.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…MacCormack [51] suggests that a valuable avenue for identifying lead (beta) customers is through exploring the company's customer-support database. Ko et al [45] also warn about the importance of selecting a sample of customers that is representative of the user community and discusses challenges when using a vocal minority of existing users.…”
Section: Customer Involvementmentioning
confidence: 99%
“…From a Requirement Engineering perspective, users' involvement via their feedback while they are using the software in practice is more credible to assess how the software is playing its role in meeting their requirements in practice [1,38,3]. In fact, many of the users' requirements are only identified after the software is being deployed and once users get the chance to use it in a real context [4]. This becomes even more evident when we consider the requirements which emerge because of the existence of competitive technology and peer pressure.…”
Section: Introductionmentioning
confidence: 99%